Sodium titanate composite zinc oxide negative electrode material, negative electrode plate and battery

The preparation of sodium titanate composite zinc oxide nanomaterial as the negative electrode material of sodium ion battery by molten salt method solves the problem of insufficient electrochemical performance of the battery and achieves a battery with high specific capacity, good conductivity and stable performance.

CN119581516APending Publication Date: 2025-03-07JIANGSU UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669818.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The electrochemical performance of sodium ion batteries is limited by problems such as excessive interface side effects, poor electron conductivity caused by wide band gaps, slow diffusion kinetics, and insufficient stability caused by lattice changes during desodiumization.

Method used

The sodium titanate composite zinc oxide nanomaterial prepared by the molten salt method is used as the negative electrode material. By mixing the sodium source, titanium source, zinc oxide and chloride salt evenly, and calcining at a temperature of 750-1000°C, a sodium titanate composite zinc oxide nanomaterial with excellent crystallinity and electrochemical properties is prepared.

Benefits of technology

The ionic conductivity of the negative electrode material of sodium ion battery is improved, the conductive connection between electrode particles is enhanced, the specific capacity and electrochemical performance of the battery is improved, and the cycle stability and rate performance of the battery is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581516A_ABST
    Figure CN119581516A_ABST
Patent Text Reader

Abstract

The invention relates to a sodium titanate composite zinc oxide negative electrode material, a negative electrode plate and a battery. The negative electrode material is a sodium titanate composite zinc oxide nano material; the chemical molecular formula of the catalyst is Na2Ti3O7 / ZnO; the preparation method comprises the following steps: uniformly mixing a sodium source, a titanium source, zinc oxide and chlorate, calcining at the temperature of 750-1000 DEG C in an air atmosphere, cleaning, separating and drying to obtain the sodium titanate composite zinc oxide nano material. The negative plate contains the sodium titanate composite zinc oxide negative electrode material. The battery comprises a battery shell, a positive plate, an isolating membrane, the negative plate and electrolyte. The sodium titanate composite zinc oxide nano material prepared by adopting a molten salt method is easy to manufacture, high in repeatability, high in raw material utilization rate and high in purity, and has excellent crystallinity and electrochemical performance; the negative plate can enhance conductive connection between the electrode particles; the battery has relatively high battery specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a sodium titanate composite zinc oxide negative electrode material, a negative electrode sheet and a battery. Background Art

[0002] Compared with the well-established lithium-ion batteries (LIBs), sodium-ion batteries (SIBs) are more attractive due to their naturally abundant sodium content, especially in applications where size / weight is not a concern, ranging from low-speed electric vehicles to large-scale off-grid energy storage. It is generally believed that Na2Ti3O7 can be converted to Na4Ti3O7 via the reversible insertion of two additional equivalent Na+ ions in the interlayer space of 2e Wyckoff sites, where 2 / 3 of the Ti(IV) ions are reduced to Ti(III), exhibiting a high capacity of 177 mAh g -1 However, the electrochemical performance, including initial Coulombic efficiency (ICE), cycling stability, and rate capability, appears to be limited by the following drawbacks: excessive interfacial side effects, poor electronic conductivity due to a wide 3.7 eV wide bandgap, sluggish diffusion kinetics, and insufficient stability caused by the inevitable lattice changes upon (de)sodiumation. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a sodium titanate composite zinc oxide negative electrode material, a negative electrode sheet and a battery. The sodium titanate composite zinc oxide nanomaterial prepared by the molten salt method is easy to manufacture, has high repeatability, high raw material utilization rate, high purity, and excellent crystallinity and electrochemical properties; the negative electrode sheet using the negative electrode material can enhance the conductive connection between the electrode particles, and the battery using the negative electrode sheet has a higher battery specific capacity.

[0004] The technical solution adopted by the present invention to solve the technical problem is: a sodium titanate composite zinc oxide negative electrode material, which is a sodium titanate composite zinc oxide nanomaterial, and the chemical molecular formula is: Na2Ti3O7 / ZnO; it is prepared by a molten salt method, specifically: a sodium source, a titanium source, zinc oxide, and a chloride salt are evenly mixed, and calcined at a temperature of 750-1000°C and an air atmosphere. After the calcination is completed, the sodium titanate composite zinc oxide nanomaterial is obtained after washing, separation, and drying.

[0005] Preferably, the atomic ratio of the sodium atoms of the sodium source, the titanium atoms of the titanium source, and the zinc atoms of zinc oxide is 2:3:(0.2-2).

[0006] Preferably, the sodium source is one of sodium molybdate, sodium carbonate, sodium sulfate, sodium phosphate, or a combination of several of them in any proportion; the titanium source is one of titanium nitrate, titanium chloride, titanium dioxide, or a combination of several of them in any proportion; and the zinc oxide is nano-grade zinc oxide.

[0007] Preferably, the molar ratio of the total amount of the sodium source, the titanium source and the zinc oxide to the chloride is (4-4.5):(100-120).

[0008] Preferably, the chloride salt is a mixture of sodium chloride and potassium chloride.

[0009] Preferably, the molar ratio of sodium chloride to potassium chloride is 10:1.

[0010] Preferably, during the mixing process of the sodium source, titanium source, zinc oxide and chloride salt, an alcohol solvent is added to assist in uniform mixing, and the mixing time is 1 to 3 hours.

[0011] Preferably, the calcination time is 10 to 20 hours.

[0012] A negative electrode sheet contains the above-mentioned sodium titanate composite zinc oxide negative electrode material.

[0013] A battery comprises a battery shell, and a positive electrode sheet, a separator, the above-mentioned negative electrode sheet, and an electrolyte located in the battery shell.

[0014] The advantages of the present invention are as follows: the present invention can improve the ionic conductivity of the sodium titanate composite zinc oxide nanomaterial as the negative electrode material of the sodium ion battery by using the molten salt method; the negative electrode material is easy to manufacture, has high repeatability and high raw material utilization rate; the negative electrode material has high purity and excellent crystallinity and electrochemical properties; the negative electrode sheet adopts the sodium titanate composite zinc oxide negative electrode material, which can enhance the conductive connection between the electrode particles; the battery manufactured by using the sodium titanate composite zinc oxide negative electrode material has a higher battery specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 This is a comparison chart of XRD tests of materials obtained in Example 1, Example 2, and Comparative Example 1;

[0016] Figure 2 This is a SEM test image of the material prepared in Example 1;

[0017] Figure 3 This is a comparison chart of the rate performance of the batteries manufactured in Example 5, Example 6, and Comparative Example 3;

[0018] Figure 4 This is a comparison chart of the cycle performance of the batteries manufactured in Example 5, Example 6, and Comparative Example 3. DETAILED DESCRIPTION

[0019] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. The embodiments are only used to explain the present invention and do not limit the protection scope of the present invention.

[0020] Unless otherwise specified, the experimental methods used below are conventional methods.

[0021] In the following examples and comparative examples, unless otherwise specified, all raw materials can be obtained by commercial purchase or conventional methods.

[0022] Embodiment 1

[0023] 1mmol of sodium carbonate, 3mmol of titanium dioxide, 0.6mmol of zinc oxide, 100mmol of sodium chloride and 10mmol of potassium chloride were put into a mortar, ethanol was added, and the mixture was ground in the mortar for 2h to be evenly mixed, and then placed in a muffle furnace, the heating rate was 5℃ / min, and the temperature was raised to 1000℃ in an air atmosphere for calcination for 20h, and then naturally cooled to room temperature, and the reaction product was soaked in deionized water, then centrifuged, placed in a blast drying oven, and dried at 110℃ for 12h to obtain a sodium titanate composite zinc oxide nanomaterial. The material is abbreviated as NTO / (ZnO)6.

[0024] Embodiment 2

[0025] 1mmol of sodium carbonate, 3mmol of titanium dioxide, 1mmol of zinc oxide, 100mmol of sodium chloride and 10mmol of potassium chloride were put into a mortar, ethanol was added, and the mixture was ground in the mortar for 2h to be evenly mixed, and then placed in a muffle furnace, the heating rate was 5℃ / min, and the temperature was raised to 1000℃ in an air atmosphere for calcination for 20h, and naturally cooled to room temperature, and the reaction product was soaked in deionized water, then centrifuged, placed in a blast drying oven, and dried at 110℃ for 12h to obtain the final product, sodium titanate composite zinc oxide nanomaterial. The material is abbreviated as NTO / (ZnO)10.

[0026] Comparative Example 1

[0027] 1mmol of sodium carbonate, 3mmol of titanium dioxide, 100mmol of sodium chloride and 10mmol of potassium chloride were put into a mortar, ethanol was added, and the mixture was ground in the mortar for 2h to be evenly mixed, and then placed in a muffle furnace, the heating rate was 5℃ / min, and the temperature was raised to 1000℃ in an air atmosphere for calcination for 20h, and naturally cooled to room temperature, and the reaction product was soaked in deionized water, then centrifuged, placed in a blast drying oven, and dried at 110℃ for 12h to obtain sodium titanate nanomaterial. This material is abbreviated as NTO.

[0028] Embodiment 3

[0029] 70 mg of the sodium titanate composite zinc oxide nanomaterial prepared in Example 1 was weighed, mixed with 20 mg of a conductive agent superP and 10 mg of a binder polyvinylidene fluoride (PVDF), and ground for 20 min, and then 0.5 mL of N-methylpyrrolidone was added and ground evenly to obtain a uniformly dispersed negative electrode material. The negative electrode material was evenly coated on a copper foil with a scraper and vacuum dried at 80° C. for 12 h to obtain a negative electrode sheet.

[0030] Embodiment 4

[0031] Weigh 70 mg of the sodium titanate composite zinc oxide nanomaterial prepared in Example 2, mix and grind with 20 mg of conductive agent superP and 10 mg of binder polyvinylidene fluoride (PVDF) for 20 min, then add 0.5 mL of N-methylpyrrolidone and continue to grind evenly to obtain a uniformly dispersed negative electrode material. The negative electrode material is evenly coated on a copper foil with a scraper and vacuum dried at 80° C. for 12 h to obtain a negative electrode sheet.

[0032] Comparative Example 2

[0033] Weigh 70 mg of the sodium titanate nanomaterial prepared in Comparative Example 1, mix and grind with 20 mg of conductive agent superP and 10 mg of binder polyvinylidene fluoride (PVDF) for 20 min, then add 0.5 mL of N-methylpyrrolidone and continue to grind evenly to obtain a uniformly dispersed negative electrode material. The negative electrode material is evenly coated on a copper foil with a scraper and vacuum dried at 80°C for 12 h to obtain a negative electrode sheet.

[0034] Embodiment 5

[0035] The negative electrode sheet of Example 3 was used, and a metal sodium sheet was used as a counter electrode to make a 2016-type button battery in a glove box filled with argon. The diaphragm used was a GF / D diaphragm, and the electrolyte used was NaClO4 / DMC:EC (volume ratio 1:1) with a concentration of 1M.

[0036] Embodiment 6

[0037] The negative electrode sheet of Example 4 was used, and a metal sodium sheet was used as a counter electrode to make a 2016-type button battery in a glove box filled with argon. The diaphragm used was a GF / D diaphragm, and the electrolyte used was NaClO4 / DMC:EC (volume ratio 1:1) with a concentration of 1 M.

[0038] Comparative Example 3

[0039] The negative electrode sheet of comparative example 2 was used, and a metal sodium sheet was used as a counter electrode to make a 2016 type button battery in a glove box filled with argon. The diaphragm used was a GF / D diaphragm, and the electrolyte used was 1M NaClO4 / DMC:EC (volume ratio 1:1).

[0040] XRD test was performed on the materials obtained in Example 1, Example 2 and Comparative Example 1; for comparison of XRD spectra, please refer to Figure 1 As shown by Figure 1 It can be seen that all diffraction peaks of sodium titanate in Comparative Example 1 [NTO] are consistent with the standard PDF card (PDF#04-009-3663-NTO); the diffraction patterns of Example 1 [NTO / (ZnO)6] and Example 2 [NTO / (ZnO)10] are similar to the standard PDF card (PDF#04-009-3663-NTO), although there are nano-sized ZnO particles on the surface. Additional diffraction peaks were observed in Example 1 [NTO / (ZnO)6] and Example 2 [NTO / (ZnO)10], which correspond to the standard PDF card (PDF#04-005-5076-ZnO).

[0041] The material prepared in Example 1 was subjected to SEM testing. Figure 2 As shown, Figure 2 The SEM surface morphology of Example 1 [NTO / (ZnO)6] is shown. Figure 2 Nanosized ZnO particles can be observed to be uniformly dispersed on the surface of sodium titanate. This ZnO coating can form a conductive network between the particles, resulting in excellent discharge / charge performance.

[0042] The 2016-type button batteries prepared in Example 5, Example 6 and Comparative Example 3 were tested for battery performance in a blue-power test system.

[0043] See also Figure 3 As shown, Figure 3 It is a rate performance diagram under different charge and discharge current densities of 0.1A / g, 0.2A / g, 0.5A / g, 1A / g, 2A / g, 5A / g, and 0.2A / g; wherein, NTO represents the battery of comparative example 3 manufactured using the material of comparative example 1; NTO / (ZnO)6 represents the battery of example 5 manufactured using the material of example 1; NTO / (ZnO)10 represents the battery of example 6 manufactured using the material of example 2.

[0044] from Figure 3 It can be observed that:

[0045] The specific capacity is about 157mAh / g, 214mAh / g, and 206mAh / g at a current of 0.1A / g; compared with undoped materials, the composited materials of the present application have good charge and discharge stability when used in batteries, and sodium ion batteries are also very stable;

[0046] The specific capacity is about 96mAh / g, 133mAh / g, and 135mAh / g at a current of 0.2A / g; compared with undoped materials, the doped materials of the present application are applied to batteries, and have good charge and discharge stability, and the sodium ion battery is also very stable;

[0047] The specific capacity is about 64 mAh / g, 93 mAh / g, and 101 mAh / g at a current of 0.5 A / g; compared with undoped materials, the doped materials of the present application are applied to batteries, and have good charge and discharge stability, and the sodium ion battery is also very stable;

[0048] The specific capacity is about 43mAh / g, 68mAh / g, and 61mAh / g at a current of 1A / g; compared with undoped materials, the doped materials of the present application are applied to batteries, and have good charge and discharge stability, and the sodium ion battery is also very stable;

[0049] The specific capacity is about 27mAh / g, 48mAh / g, and 34mAh / g at a current of 2A / g; compared with undoped materials, the doped materials of the present application are applied to batteries, and have good charge and discharge stability, and sodium ion batteries are also very stable;

[0050] The specific capacity is about 15 mAh / g, 30 mAh / g, and 17 mAh / g at a current of 5 A / g; compared with undoped materials, the doped materials of the present application are applied to batteries, and have good charge and discharge stability, and sodium ion batteries are also very stable;

[0051] Back to the current of 0.2A / g, the specific capacity is about 89mAh / g, 114mAh / g, and 120mAh / g. Compared with the undoped material, the doped material of the present application is used in the battery, and has good charge and discharge stability, and the sodium ion battery is also very stable.

[0052] The comparison of the above data is shown in the table below.

[0053]

[0054] Through the test of rate performance, it can be found that the battery prepared by using the negative electrode sheet containing the sodium titanate composite zinc oxide nanomaterial of the present invention has good electrochemical performance, good battery rate performance and high coulombic efficiency.

[0055] See also Figure 4 As shown, Figure 4The performance diagram of the battery after 70 cycles at a current density of 0.2 A / g. Among them, NTO represents the battery of comparative example 3 manufactured using the material of comparative example 1; NTO / (ZnO)6 represents the battery of example 5 manufactured using the material of example 1; NTO / (ZnO)10 represents the battery of example 6 manufactured using the material of example 2.

[0056] from Figure 4 It can be observed that compared with the sodium titanate nanomaterial not compounded with zinc oxide in comparative example 1, the batteries of the sodium titanate compounded with zinc oxide nanomaterial used in examples 5 and 6 have better cycle stability performance.

[0057] The above embodiments should not limit the present invention in any way, and any technical solutions obtained by equivalent replacement or equivalent conversion shall fall within the protection scope of the present invention.

Claims

1. A sodium titanate composite zinc oxide negative electrode material, characterized in that: It is a sodium titanate composite zinc oxide nanomaterial with a chemical formula of Na2Ti3O7 / ZnO. It is prepared by a molten salt method, specifically, a sodium source, a titanium source, zinc oxide, and a chloride salt are uniformly mixed, and calcined at a temperature of 750 to 1000°C in an air atmosphere. After the calcination, the sodium titanate composite zinc oxide nanomaterial is obtained after washing, separation, and drying.

2. The sodium titanate composite zinc oxide negative electrode material according to claim 1, characterized in that: The atomic ratio of the sodium atoms of the sodium source, the titanium atoms of the titanium source, and the zinc atoms of the zinc oxide is 2:3:(0.2-2).

3. A sodium titanate composite zinc oxide negative electrode material according to claim 1 or 2, characterized in that: The sodium source is one of sodium molybdate, sodium carbonate, sodium sulfate, sodium phosphate or a combination of several of them in any proportion; the titanium source is one of titanium nitrate, titanium chloride, titanium dioxide or a combination of several of them in any proportion; the zinc oxide is nano-grade zinc oxide.

4. The sodium titanate composite zinc oxide negative electrode material according to claim 1, characterized in that: The molar ratio of the total amount of the sodium source, the titanium source and the zinc oxide to the chloride salt is (4-4.5):(100-120).

5. A sodium titanate composite zinc oxide negative electrode material according to claim 1 or 4, characterized in that: The chloride salt is a mixture of sodium chloride and potassium chloride.

6. The sodium titanate composite zinc oxide negative electrode material according to claim 5, characterized in that: The molar ratio of sodium chloride to potassium chloride is 10:

1.

7. The sodium titanate composite zinc oxide negative electrode material according to claim 1, characterized in that: During the mixing process of the sodium source, titanium source, zinc oxide and chloride salt, an alcohol solvent is added to assist in uniform mixing, and the mixing time is 1 to 3 hours.

8. The sodium titanate composite zinc oxide negative electrode material according to claim 1, characterized in that: The calcination time is 10 to 20 hours.

9. A negative electrode sheet, characterized in that: Contains the sodium titanate composite zinc oxide negative electrode material as described in any one of claims 1 to 8.

10. A battery, characterized in that: The invention comprises a battery shell, a positive electrode sheet, a separator, a negative electrode sheet as claimed in claim 9, and an electrolyte located in the battery shell.